Study on aquagas welding / Md Fakarudin Ab Rahman, Mohd Al-Rashidin Mohd Rashid and Helmy Rohaizad Hamzah - Ab Rahman, Md Fakarudin; Mohd Rashid, Mohd Al-Rashidin; Hamzah, Helmy Rohaizad (1999)
The "Study On AquaGas Welding" generally, to gain knowledge and experience in this new technology in the world of welding and able to report our experience on the advantages, disadvantages and the difficulty that used faced while using it as compared to that of oxy-acetylene welding process